2013
DOI: 10.1186/1476-511x-12-22
|View full text |Cite
|
Sign up to set email alerts
|

Butylated hydroxytoluene can protect polyunsaturated fatty acids in dried blood spots from degradation for up to 8 weeks at room temperature

Abstract: BackgroundDried blood spots (DBS) from fingertip prick blood can enable high throughput fatty acid profiling but may be prone to lipid peroxidation during storage. The use of butylated hydroxytoluene (BHT) on chromatography paper can prevent polyunsaturated fatty acid (PUFA) loss but examinations on the length of storage times possible are not comprehensive.MethodIn the first study, venous whole blood was saturated on paper strips pre-soaked with 0, 2.5 or 5.0 mg/mL BHT and exposed to air for up to 28 days. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 30 publications
2
38
1
Order By: Relevance
“…Furthermore, we chose to conduct many of our experiments on blood from an individual who was a long time consumer of high dose fish oil to deliberately subject our methodology to the magnification of having high blood levels (>15%) of n-3 LCPUFA. This is contrast to other reports [11,14] where the blood n-3 LCPUFA levels are only ~5% of the total fatty acids, such that small decreases in n-3 LCPUFA would be hard to detect.…”
Section: Discussioncontrasting
confidence: 51%
See 3 more Smart Citations
“…Furthermore, we chose to conduct many of our experiments on blood from an individual who was a long time consumer of high dose fish oil to deliberately subject our methodology to the magnification of having high blood levels (>15%) of n-3 LCPUFA. This is contrast to other reports [11,14] where the blood n-3 LCPUFA levels are only ~5% of the total fatty acids, such that small decreases in n-3 LCPUFA would be hard to detect.…”
Section: Discussioncontrasting
confidence: 51%
“…Many of the reports claiming stable DBS methodology in profiling fatty acids are flawed by the use of inappropriate controls or using bloods with low levels of n-3 LCPUFA so that small changes would not have been detected [7,8,11,14,15]. Some studies [7,11,15] have taken as their zero time point a sample of blood that has been recently spotted onto filter paper and dried in air, a process we have shown here to result in significant losses in n-3 LCPUFA even in the presence of an antioxidant (Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Minimal changes in PUFA wt% were observed when samples were at room temperature for 5 days [21] or after two weeks [5]. The instabilities of fatty acid compositions in dried blood increased during long-term storage of up to 6 months, as reported in several studies [8, 10, 30]. A recent study on the long-term stabilities of fatty acids reported that pre-conditioning the filter paper with a higher concentration of BHT solution (5 mg/mL) could effectively maintain the n-3 % HUFA of dried blood, when stored at room temperature for 28 days [30].…”
Section: Discussionmentioning
confidence: 92%